2019
DOI: 10.1590/0004-282x20190069
|View full text |Cite
|
Sign up to set email alerts
|

Association of bruxism and anxiety symptoms among military firefighters with frequent episodic tension type headache and temporomandibular disorders

Abstract: Objective To assess the presence of bruxism and anxiety among military firefighters with frequent episodic tension-type headache and painful temporomandibular disorders (TMDs). Methods The sample consisted of 162 individuals aged 18 to 55 years divided into four groups. Headache was diagnosed in accordance with the International Classification of Headache Disorders-III. The Research Diagnostic Criteria for Temporomandibular Disorders questionnaire was used to classify TMDs and awake bruxism; sleep bruxism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Still, self-report is a method used by other studies in recent years for diagnosing possible AB, [40][41][42][43] as well as for identifying individuals with headaches. 9,[43][44][45][46] Also, the use of a convenience sample can be considered a limitation, as individuals were not selected using statistical criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, self-report is a method used by other studies in recent years for diagnosing possible AB, [40][41][42][43] as well as for identifying individuals with headaches. 9,[43][44][45][46] Also, the use of a convenience sample can be considered a limitation, as individuals were not selected using statistical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the retrospective nature of this study did not allow adding new questions or clinical examination for a more accurate diagnosis. Still, self‐report is a method used by other studies in recent years for diagnosing possible AB, 40–43 as well as for identifying individuals with headaches 9,43–46 . Also, the use of a convenience sample can be considered a limitation, as individuals were not selected using statistical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This tool is also rarely considered for use because it is considered to have only a small impact on the medical world. 8,9,10 According to Bandodkar (2021) age affects bruxism, this is proven in a study that divided groups of respondents based on their age it was found that the prevalence of bruxism was higher in patients who had an age group of 30 years (56.7%) than patients in the age group of 31-35 years (26.7%) and patients over the age of 35 years (16.7%) in this study, this is because the 30-yearold group experiences more pressure in work and the environment that can cause psychological disorders that affect the occurrence of depression. bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…further in the temporomandibular joint and teeth or the surrounding area. 8,18 Can be concluded that anxiety and bruxism that occur in adults have a relationship. Bruxism is a response that arises as a result of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation